2020
DOI: 10.15644/asc54/3/3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Effects of Single and Combined use of Different Irrigation Solutions Against Intracanal Enterococcus Faecalis

Abstract: Objectives This study assessed the antibacterial activity of both separate and combined uses of 5.25% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 17% ethylenediaminetetraacetic acid (EDTA), 3% hydrogen peroxide (H 2 O 2 ), MTAD, SmearClear (SC) and 13.8% chlorine dioxide (ClO 2 ) irrigation solutions against Enterococcus faecalis. Materials and Methods Two hundred e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Micro-CT studies have shown that in round canals, between 10% and 50% of their total area remains unprepared [40]. When using instrumentation on the root canal system, approximately 30% of the endodontic space remains unprepared [41,42]. Such spaces may contain residual pulp or bacterial biofilm in infected canals, thus exerting adverse effects on treatment outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT studies have shown that in round canals, between 10% and 50% of their total area remains unprepared [40]. When using instrumentation on the root canal system, approximately 30% of the endodontic space remains unprepared [41,42]. Such spaces may contain residual pulp or bacterial biofilm in infected canals, thus exerting adverse effects on treatment outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…In order to make comparison and meta-analysis more effective for past and future studies, human single-rooted teeth were preferred in our study. In addition, wide and straight canals in this type of single-rooted teeth enable irrigation solution application research and activation efficiency research to be carried out in laboratory environments in a more standardized manner [ 8 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium hypochlorite (NaOCl) is currently the most widely used irrigation solution, especially due to its solvent effect on pulp tissue, high antibacterial activity, and lubricating properties [ 8 ]; however, its cytotoxicity at high concentrations and inadequacy in removing the smear layer alone have led to research into alternative solutions [ 8 ]. For this purpose, solutions such as boric acid (BA), chlorine dioxide (ClO 2 ), and hypochlorous acid (HOCl) continue to be evaluated for their potential as irrigation solutions due to their different properties [ 8 – 10 ]. Additionally, due to its inadequacy in removing the smear layer alone, it is necessary to use two or more irrigation solutions sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that these regions in the root canal system are left untouched during mechanical instrumentation [3][4][5][6], which makes the goal of endodontic therapy unlikely to be achieved with mechanical instrumentation alone. As a result, chemical irrigants are essential for disinfecting these complicated root canal anatomies [7]. An ideal irrigant should have strong antibacterial properties, dissolve any remaining pulp tissues without posing systemic health risks, and be readily available [8].…”
Section: Introductionmentioning
confidence: 99%